RESEPSI MASYARAKAT MILENIAL TERHADAP PESAN DAKWAH MELALUI MEDIA SOSIAL DI KABUPATEN BONE - Sulfika Sulfika (Jurnal Dakwah Tabligh, 2020)
The main problem in this study is the acceptance of millennial society towards the message of da'wah through social media in Bone District? The subject matter is then divided into several subproblems or research questions, namely: 1) What is the multimedia propaganda model on social media? This type of research is classified as phenomenology with methodological (qualitative) and scientific approaches (Communication, Da'wah and Sociology). Furthermore the data collection methods used are in-depth interviews, observation and documentation. Then, data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and drawing conclusions. The results of this study indicate that the multimedia propaganda model on social media currently has many variations that allow people to listen to preaching whenever and wherever they are. Among the models of preaching include: Audio Visual / video, Images and Animation. Audio visual is a da'wah model that displays sound and images (in video format). Some social media users feel the rampant Islamic material they read on social media links, make them more interested in studying Islam, feel they have a better understanding of Islam, and feel their daily behavior is becoming more in line with Islamic guidance. Islamic material on social media is also considered helpful for those who feel they have limited time to attend the study forums.